TINJAUAN YURIDIS PELAKSANAAN PEMBATALAN PERKAWINAN DI PENGADILAN AGAMA - Suwardi Suwardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In the provisions of the law, marriage must be carried out in accordance with the terms and conditions of marriage. One of the conditions of the marriage is an agreement between the parties who wish to marry, including knowing the identity of each party. This means that a marriage is prohibited if it does not meet the requirements, while such a marriage which has already been carried out can be canceled. In the writing of this thesis, research was carried out on problems in the form of the process of implementing an application for a marriage cancellation case at the Religious Court and the legal consequences of cancellation of marriage on children and joint assets. In the research method used was normative juridical. The procedure for filing a cancellation request at the Religious Court begins with registration of the application and goes through several administrative processes which are then followed by a trial where at the first trial the panel of judges is obliged to reconcile the applicant with the respondent, furthermore, the cancellation of the marriage has a legal effect on the relationship between the applicant and the respondent which is no longer bound by ties. a legal and essential marriage, and there is no civil obligation for the applicant or the respondent.